2022
DOI: 10.3389/fnins.2022.780407
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Restricted Behaviors in Autism Spectrum Disorder: From Mechanism to Development of Therapeutics

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder characterized by deficits in social communication, social interaction, and repetitive restricted behaviors (RRBs). It is usually detected in early childhood. RRBs are behavioral patterns characterized by repetition, inflexibility, invariance, inappropriateness, and frequent lack of obvious function or specific purpose. To date, the classification of RRBs is contentious. Understanding the potential mechanisms of RRBs in children with ASD, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 356 publications
(421 reference statements)
0
19
0
Order By: Relevance
“…This is an interesting finding because previous research has indicated that repetitive behaviors can be subdivided into restrictive/repetitive sensory motor behaviors and insistence on sameness behaviors ( Cuccaro et al, 2003 ; Bishop et al, 2013 ), which in other publications have been classified as low-order (restricted) and high-order (sameness) behaviors ( Turner, 1999 ). Restricted behaviors can include dyskinesia, convulsions, and repeated manipulation of objects, while sameness behavior refers to a general insistence on routine consistency ( Tian et al, 2022 ). The discriminant coefficients indicate these two subscales are representative of opposite group membership, where greater deficits in restricted behaviors are associated with ASD males and greater deficits in sameness behaviors are associated with ASD females.…”
Section: Discussionmentioning
confidence: 99%
“…This is an interesting finding because previous research has indicated that repetitive behaviors can be subdivided into restrictive/repetitive sensory motor behaviors and insistence on sameness behaviors ( Cuccaro et al, 2003 ; Bishop et al, 2013 ), which in other publications have been classified as low-order (restricted) and high-order (sameness) behaviors ( Turner, 1999 ). Restricted behaviors can include dyskinesia, convulsions, and repeated manipulation of objects, while sameness behavior refers to a general insistence on routine consistency ( Tian et al, 2022 ). The discriminant coefficients indicate these two subscales are representative of opposite group membership, where greater deficits in restricted behaviors are associated with ASD males and greater deficits in sameness behaviors are associated with ASD females.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the discussed motor and nonmotor functions of the STN, especially its role in action inhibition, we argue that it probably plays an important, yet underexplored role in NDDs. For example, ASD, ADHD, Tourette’s syndrome, and schizophrenia are all characterized by restricted and repetitive patterns of behavior (RRBs) like stereotypies, perseveration, and tics, which are basically disorders of behavioral control ( Lewis et al, 2018 ; Vicente et al, 2020 ; Tian et al, 2022 ). Additionally, RRBs could be just behavioral manifestations of a broader cognitive inflexibility and an inability to stop unwanted actions or thoughts ( Tian et al, 2022 ).…”
Section: Clinical Importance Of Stnmentioning
confidence: 99%
“…For example, ASD, ADHD, Tourette’s syndrome, and schizophrenia are all characterized by restricted and repetitive patterns of behavior (RRBs) like stereotypies, perseveration, and tics, which are basically disorders of behavioral control ( Lewis et al, 2018 ; Vicente et al, 2020 ; Tian et al, 2022 ). Additionally, RRBs could be just behavioral manifestations of a broader cognitive inflexibility and an inability to stop unwanted actions or thoughts ( Tian et al, 2022 ). However, clinical and preclinical neuroimaging studies have not studied intra-basal ganglia connectivity or possible abnormalities of small nuclei like STN in RRBs (for review, see Wilkes and Lewis, 2018 ), although animal models demonstrated clear involvement of STN in stereotyped behavior ( Chang et al, 2016 ; Lewis et al, 2018 ; Wilkes and Lewis, 2018 ).…”
Section: Clinical Importance Of Stnmentioning
confidence: 99%
“…The pathogenesis of ASD is not fully clarified. It seems that it is caused by genetic factors affecting neural connectivity, consequently impairing social communication development and leading to stereotypies and restricted interests [1,2]. It has been hypothesized that the heterogeneous clinical presentation of ASD results from the interaction between multiple genes or gene combinations as well as epigenetic factors and exposure to environmental modifiers [3].…”
Section: Introductionmentioning
confidence: 99%